Ovulation synchronization following commercial application of ultrasound-guided follicle ablation during the estrous cycle in mares - Bergfelt, D. R.; Meira, Cezinande de [UNESP]; Fleury, J. J.; Fleury, P. D. C.; Dell'aqua Junior, José Antônio [UNESP]; Adams, G. P. (Elsevier B.V., 2007)
A regimen of progesterone plus estradiol (P&E) was used as a standard for ovarian synchronization to test the efficacy and evaluate the commercial application of ultrasound-guided follicle ablation as a non-steroidal alternative for ovulation synchronization in mares. Recipient mares at a private embryo transfer facility were at unknown stages of the estrous cycle at the start of the experiment on Day 1 when they were randomly assigned to an ablation group (n = 18-21 mares) or to a ME group (n = 20-21 mares). In the ablation group, mares were lightly sedated and all follicles > 10 mm were removed by transvaginal ultrasound-guided follicle aspiration. In the ME group, a combination of progesterone (150 mg) plus estradiol (10 mg) prepared in safflower oil was given daily (im) for 10 d. Two doses of prostaglandin FZ, (PGF, 10 mg/dose, im) were given 12 h apart on Day 5 in the ablation group, or a single dose on Day 10 in the ME group. Human chorionic gonadotropin (hCG, 2500 IU/mare, im) was given at a fixed time, 6 and 10 d after PGF treatment in the ablation and ME groups, respectively, with the expectation of a follicle > 30 mm at the time of treatment. In both the ablation and P&E groups, transrectal ultrasonography was done at the start of the study (Day 1) and again on the day of hCG treatment and daily thereafter to determine the presence of a CL, measure diameter of the largest follicle and detect ovulation. The mean interval from the start of the study and from PGF treatment to ovulation was shorter (P < 0.0001) in the ablation group (13.7 and 9.7 d, respectively) compared to the P&E group (22.3 and 13.2 d, respectively). Following fixed-day treatment with hCG after PGF treatment, the degree of ovulation synchronization was not different (P > 0.05) between the ablation and P&E groups within a 2-d (56 and 70%) or 4-d (83% and 90%) period. Although ultrasound-guided follicle ablation may not be practical in all circumstances, it excluded the conventional 10-d regimen of progesterone and estradiol and was considered an efficacious and feasible, non-steroidal alternative for ovulation synchronization in mares during the estrous cycle. (C 2007 Elsevier B.V. All rights reserved.
Keywords: follicle ablation; progesterone plus estradiol; ovulation synchronization; mare